2015
DOI: 10.1016/j.wem.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Involvement and Hepatocellular Injury Caused by a Snake With Hematotoxin Envenomation

Abstract: Venomous snakes with hematotoxin-Russell's viper (Daboia spp), Malayan pit viper (Calloselasma rhodostoma), and green pit viper (Cryptelytrops albolabris and C macrops, previously named Trimeresurus spp) are commonly found in Thailand. Coagulation factor activation, thrombocytopenia, hyperfibrinolysis, and disseminated intravascular coagulation are the main mechanisms of hemorrhaging from these snake bites. The neurological involvement and hepatocellular injury after Russell's viper bites were reported in Sri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It can be an important differentiating clinical feature between cobra and krait bite, rarely Russell viper bite may present with ptosis and cellulitis. (11,12) Treatment for snakebite patient is local care of the bitten site and anti-snake venom (ASV). In a study on Snake envenomation in a north Indian hospital Sharma N found that the mean dose of antivenom used for neuroparalytic snakebite was 51.2 vials (Range=5-190 vials) and 32 vials (Range=1-130 vials) for viper bites.…”
Section: Discussionmentioning
confidence: 99%
“…It can be an important differentiating clinical feature between cobra and krait bite, rarely Russell viper bite may present with ptosis and cellulitis. (11,12) Treatment for snakebite patient is local care of the bitten site and anti-snake venom (ASV). In a study on Snake envenomation in a north Indian hospital Sharma N found that the mean dose of antivenom used for neuroparalytic snakebite was 51.2 vials (Range=5-190 vials) and 32 vials (Range=1-130 vials) for viper bites.…”
Section: Discussionmentioning
confidence: 99%